Curvature Inheritance Symmetry of C_9-manifolds - Humam T. S. Al-Attwani - - Mohammed Y. Abass ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
This paper focused on Riemannian curvature tensor  of manifolds. The components of covariant derivative of  determined on the space of structure. There are fifteen non-zero of such components and the others components given by the symmetry property and Bianchi identity of . According to these components, the conditions on curvature tensor  of manifolds to be has inheritance symmetry established. These conditions summarized by five equations that have common arbitrary scalar function